Development of Multiplication Board Media Using the ADDIE Model to Improve Elementary Students’ Mathematics Learning Outcomes - Zia Arfina Taufani; Sudarsri Lestari; Vina Rohmatul Ummah (Journal of Educational Management Research, 2026)
This study aims to develop and examine the feasibility and effectiveness of multiplication board media in improving mathematics learning outcomes among third-grade students. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and pretest-posttest assessments. The subjects involved material and media experts as validators and third-grade students as research participants. Data analysis was conducted descriptively, while the effectiveness of the developed media was evaluated using the Wilcoxon Signed Rank Test and N-Gain analysis. The results showed that the multiplication board media achieved a feasibility score of 95% from material experts and 85% from media experts, indicating a highly feasible and feasible category, respectively. Student responses demonstrated a very positive perception, with scores ranging from 80% to 90%. The Wilcoxon test showed a significance value of <0.001, and the average N-Gain score of 0.6872 (68.72%) indicated a moderate level of effectiveness. This study implies that multiplication board media can serve as an innovative and practical learning tool to support conceptual understanding and improve students’ mathematics learning outcomes.